Narasi-narasi Kecil (Mikronarasi) dalam genre Fiksi Pedesaan Pendekatan Posmodernisme terhadap Cerpen Menghilang Bersama Angin karya Xing Qingjie - Konistiawati, Stevani; Gunawan, Hin Goan (Bambuti, 2020)
The short story text Disappearing with the Wind by Xing Qingjie as a representation of the rural fiction genre in Chinese Literature attempts to refute the grand narratives of modern fiction. For the author of the text, the power of modernity is not eternal, but can be subverted or deconstructed by giving acknowledgment to the small voices represented by Mr Zou, Sha Xiaobao, and the idiot woman in Disappearing with the Wind. This study uses a postmodernism approach to map the elements of disorientation, abnormality and small voices in that short story. Affirmation of the micronarrative is a way of working of postmodern fiction in challenging the power of modernity with the grand narrative as its main basis. For Xing Qingjie, reality does not always depend on big people, famous people, but can also be celebrated by village people, unusual people, including people who are marginalized in modern life. In his lawsuit, the presence of this text will emphasize that there is no central, no peripheral. All can be the center, and all can also be the periphery. Rural fiction pioneered by Lu Xun proves that denial of the power of grand narratives is possible in the same way that Xing Qingjie has done in a number of his works, including the short story Disappearing with the Wind.